Safety Helmet with Collision Detection System - Zohari, Mohd Hakimi; Muhammad Lokman Mohamad Elias; Najib Mohammed Ahmed Al-Fadhali (Journal of Advanced Industrial Technology and Application, 2024)
A comprehensive smart helmet system integrating various sensors and communication modules has been developed for enhancing safety and functionality during motorcycle rides. The research addresses the critical issue of road safety for motorcyclists by introducing an accident detection system using accelerometers and gyroscopes, coupled with an emergency response system. The implementation utilizes an ESP32 microcontroller, MPU6050 sensor, GSM module, and GPS module. The findings showcase the effectiveness of the collision detection system and its potential to significantly improve emergency response times. The abstract underscores the importance of such technological interventions in reducing accident-related fatalities and injuries among motorcyclists. The discussion emphasizes the need for wider adoption of similar smart helmet systems and highlights the potential for future enhancements in both hardware and software components. The outcomes suggest a paradigm shift in motorcycle safety measures, urging policymakers and manufacturers to consider integrating these technologies into standard safety protocols.